The interplay of climate change and physical activity: Implications for cardiovascular health - Eloise J. Thompson; Sarah E. Alexander; Kegan Moneghetti; Erin J. Howden (American Heart Journal Plus)
Cardiovascular disease (CVD) is one of the top contributors to global disease burden. Meeting the physical activity guidelines can effectively control and prevent several CVD risk factors, including obesity, hypertension and diabetes mellitus. The effects of climate change are multifactorial and have direct impacts on cardiovascular health. Increasing ambient temperatures, worsening air and water quality and urbanisation and loss of greenspace will also have indirect effects of cardiovascular health by impacting the ability and opportunity to participate in physical activity. A changing climate also has implications for large scale sporting events and policies regarding risk mitigation during exercise in hot climates. This review will discuss the impact of a changing climate on cardiovascular health and physical activity and the implications for the future of organised sport.